WIMP Dark Matter Searches With the ATLAS Detector at the LHC - Giagu, Stefano (Frontiers in Physics, 2019)
Astronomical and cosmological observations support the existence of invisible matter that can only be detected through its gravitational effects, thus making it very difficult to study. Dark Matter makes up about 27% of the known universe. As a matter of fact, one of the main goals of the physics programme of the experiments at the Large Hadron Collider of the CERN laboratory, is the search of new particles that can explain the Dark Matter. This review discusses both experimental and theoretical aspects of searches of Weakly Interacting Massive Particles candidates for dark matter at the LHC. An updated overview of the various experimental search channels performed by the ATLAS experiment is presented, in order to pinpoint complementarity among different types of LHC searches and the interplay between LHC and direct and indirect Dark Matter searches